Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/09564624211030766
|View full text |Cite
|
Sign up to set email alerts
|

Longer duration of anti-retroviral therapy is associated with decreased risk of human papillomaviruses detection in Kenyan women living with HIV

Abstract: Objective: A longitudinal study was conducted among women living with HIV in Kenya to determine if duration of anti-retroviral (ART) usage altered detection and persistence of oncogenic (high-risk) human papillomaviruses (HR-HPV). Methods: Women living with HIV without cervical dysplasia were enrolled at a cervical cancer screening clinic. Three cervical swabs, HIV viral loads, and CD4 cell counts were obtained at enrollment and at two annual visits. HPV genotyping was performed on swabs (Roche Linear Array). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Different researchers reported a lower prevalence of cervix HPV infection in PLWH receiving ART compared to untreated patients. 145 In addition, a longer duration of ART among women was associated with a lower prevalence of HR-HPV infection in Kenya 146 suggesting higher immune control and clearance of HPV infection in the cervix. 145 Lower progression risk from low-grade squamous intraepithelial lesions to high-grade squamous intraepithelial lesions was reported among women who used ART.…”
Section: Relationship Between Antiretroviral Therapy (Art) and Hpvmentioning
confidence: 99%
“…Different researchers reported a lower prevalence of cervix HPV infection in PLWH receiving ART compared to untreated patients. 145 In addition, a longer duration of ART among women was associated with a lower prevalence of HR-HPV infection in Kenya 146 suggesting higher immune control and clearance of HPV infection in the cervix. 145 Lower progression risk from low-grade squamous intraepithelial lesions to high-grade squamous intraepithelial lesions was reported among women who used ART.…”
Section: Relationship Between Antiretroviral Therapy (Art) and Hpvmentioning
confidence: 99%
“…Notwithstanding these significant methodologic limitations, meta‐analyses of the available literature suggest that WLWH have a higher risk of HPV acquisition, presumably due to shared behavioral risk of sexual transmission but also likely due to immune dysregulation (presumably because more incident HPV infections, even those destined to clear, persist long enough to be detected 42 , 43 ), as evidenced by the inverse association between HPV acquisition risk and markers of HIV control/immune status (eg, CD4 counts). 43 , 44 , 45 WLWH have an approximately ≥2‐fold prevalence of HPV compared with HIV‐negative women.…”
Section: Impact Of Hiv and Hiv Control On Hpv Natural Historymentioning
confidence: 99%
“…Notwithstanding these significant methodologic limitations, meta‐analyses of the available literature suggest that WLWH have a higher risk of HPV acquisition, presumably due to shared behavioral risk of sexual transmission but also likely due to immune dysregulation (presumably because more incident HPV infections, even those destined to clear, persist long enough to be detected 42 , 43 ), as evidenced by the inverse association between HPV acquisition risk and markers of HIV control/immune status (eg, CD4 counts). 43 , 44 , 45 WLWH have an approximately ≥2‐fold prevalence of HPV compared with HIV‐negative women. 46 , 47 , 48 , 49 , 50 , 51 , 52 Among WLWH, HPV prevalence was lower among those receiving ART (vs not), 51 , 53 , 54 , 55 , 56 , 57 , 58 , 59 on longer (vs shorter) duration of ART, 20 , 54 with higher (vs lower) CD4 counts, 51 , 54 , 55 , 56 , 57 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 and with a lower HIV viral load.…”
Section: Impact Of Hiv and Hiv Control On Hpv Natural Historymentioning
confidence: 99%
“…A meta-analysis including 6500 women infected by HIV reported a lower HR-HPV prevalence in the pooled analysis than in those not receiving ART (with a crude OR of 0·82) [ 71 ]. In addition, an observational study conducted in Kenya also reported that a longer duration of ART was associated with a lower HPV infection prevalence of all HPV genotypes and HR-HPV specifically (with ORs, of 0.90 and 0.87, respectively) [ 72 ]. This could reflect better immune control and viral clearance of HPV infection in the cervix among women receiving ART, changes in risky sexual behaviors, or a combination of both.…”
Section: Relationship Between Antiretroviral Therapy and Hpvmentioning
confidence: 99%